A diffusion-coupled cohesive element model for cracking analysis of thermal barrier coatings. (1st April 2021) - Song, Jianan; Qi, Hongyu; Li, Shaolin; Yang, Xiaoguang; Shi, Duoqi; Fei, Chengwei
Highlights: A diffusion-coupled cohesive element model (DCZM) was proposed and applied on FE models. Effect of diffusion on the stress distributions and cracks propagation in TBCs was investigated. Cracking behavior of TBCs with different strength sensibility were analyzed. Abstract: The diffusion of Al from the bond-coat (BC) causes a continuous thickening of thermal-growth-oxide (TGO) layer, resulting in increased interface stresses at the interface of top-coat (TC) and BC. Moreover, the formation of TGO results in Al depletion in the BC layer. The presence of Ni, Co, Cr, and Al porous oxide combination may degrade the thermal barrier coating system (TBCs) interface. In this paper, a diffusion-coupled cohesive zone model (DCZM) is proposed to analyze the stress distributions and cracking behaviors in TBCs. The simulation methodology considers the thermal mismatch stress, oxidation growth stress, and diffusion-induced strength degradation. The results indicate that the Al diffusion increased the tensile stress on the interface by 4.2% in each cycle, and the failure time for TBCs was observed approximately 10% lesser than that of non-diffusion models. Furthermore, the interface with higher degradation sensibility has a shorter crack initiation life.